2021
DOI: 10.1002/adma.202008161
|View full text |Cite
|
Sign up to set email alerts
|

Mechanosensation Mediates Long‐Range Spatial Decision‐Making in an Aneural Organism

Abstract: The unicellular protist Physarum polycephalum is an important emerging model for understanding how aneural organisms process information toward adaptive behavior. Here, it is revealed that Physarum can use mechanosensation to reliably make decisions about distant objects in its environment, preferentially growing in the direction of heavier, substratedeforming, but chemically inert masses. This long-range sensing is abolished by gentle rhythmic mechanical disruption, changing substrate stiffness, or the additi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…Cells and their components have many competencies for adaptive behavior when navigating physiological, metabolic, and transcriptional spaces [86]. Examples include the ability of gene-regulatory networks and chemical pathways to learn from experience [87][88][89], for transcriptional machinery to rapidly adjust to compensate for entirely novel physiological stressors [90], and for unicellular slime molds to explore their environment at a distance and make decisions using memory and comparison of alternatives [91][92][93][94][95].…”
Section: Developmental Plasticity and Evolution Todaymentioning
confidence: 99%
“…Cells and their components have many competencies for adaptive behavior when navigating physiological, metabolic, and transcriptional spaces [86]. Examples include the ability of gene-regulatory networks and chemical pathways to learn from experience [87][88][89], for transcriptional machinery to rapidly adjust to compensate for entirely novel physiological stressors [90], and for unicellular slime molds to explore their environment at a distance and make decisions using memory and comparison of alternatives [91][92][93][94][95].…”
Section: Developmental Plasticity and Evolution Todaymentioning
confidence: 99%
“…Indeed, since the seminal contribution of Toshiyuki Nakagaki and colleagues more than 20 years ago [33], P. polycephalum has become an essential model organism for studying problem-solving in non-neural systems [32][33][34][35][36][37]. Past experiments have shown that acellular slime moulds can find the shortest path in a maze [33,38], build optimized networks to connect several food sources [34], anticipate events [39], learn to ignore irrelevant stimuli [40,41], encode memory in their environment [42] or in their morphology [43], interact with their congeners [21,44], optimize nutrient intake [28,45], make optimal decisions [27,29,46], etc. Physarum polycephalum's behaviour relies on its self-organized internal architecture, which consists of a transport network of interconnected tubes [47].…”
Section: Introductionmentioning
confidence: 99%
“…Physarum polycephalum can migrate at a speed of up to few millimetres per hour through the interplay of intracellular flow, adhesion and rhythmic contractions of the tubes [48][49][50]. The frequency and the amplitude of the contractions depend on external stimuli, and, as a result, P. polycephalum is capable of altering its shape and motion as a function of a variety of external stimuli such as chemicals [51][52][53], light [54], temperature [55][56][57], humidity [44], gravity [58] or substrate distortion [46].…”
Section: Introductionmentioning
confidence: 99%
“…To understand the intelligence and decision-making capabilities of P.polycephalum, various experimental studies have been conducted to control the movement of P.polycephalum. ,, As one of the methodological examples of P.polycephalum guidance, organism was placed in a dish and exposed to a light source at a specific area . The organism was able to navigate toward the light source, demonstrating its ability to sense and respond to light.…”
Section: Introductionmentioning
confidence: 99%